Financial Constraint on R&D Activities in Vietnamese Universities – an Empirical Research - Tue, Nguyen Dang (Organizations and Markets in Emerging Economies, 2020)
R&D is one of the most important roles of universities. Many previous studies examined the impact of financial factor on university R&D activities but reached no consensus view. This article contributes to the current literature by exploring how financial factor and other factors influence R&D activities in Vietnamese universities. The author employed a survey dataset from the Association of Vietnam universities and colleges to check whether unfavourable financial condition hindered university R&D activities. Using structural equation modelling, the author found empirical evidence that financial constraint could hamper R&D productivity. On the other hand, favourable conditions in management, communication, infrastructure and human resources were found to improve R&D activities. This led to some policy suggestions to improve R&D activities in Vietnam higher education institutions.